2010
DOI: 10.1111/j.1365-2672.2010.04874.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of ceragenin CSA-13 and its mixture with pluronic F-127 as treatment of topical bacterial infections

Abstract: Aims Ceragenin CSA-13 is a synthetic mimic of cationic antibacterial peptides, with facial amphiphilic morphology reproduced using a cholic acid scaffold. Previous data have shown that this molecule displays broad-spectrum antibacterial activity, which decreases in the presence of blood plasma. However, at higher concentrations, CSA-13 can cause lysis of erythrocytes. This study was designed to assess in vitro antibacterial and haemolytic activity of CSA-13 in the presence of pluronic F-127. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 43 publications
8
49
0
1
Order By: Relevance
“…The amphiphilic nature of ceragenins allows them to associate well with micelles, and Nagant et al [78] and Leszczynska et al [88] studied the effects of pluronic F-127 on the cytotoxicity of ceragenins. They found that micelles derived from pluronic F-127 decreased cytotoxicity toward eukaryotic cells and possibly improved antimicrobial activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amphiphilic nature of ceragenins allows them to associate well with micelles, and Nagant et al [78] and Leszczynska et al [88] studied the effects of pluronic F-127 on the cytotoxicity of ceragenins. They found that micelles derived from pluronic F-127 decreased cytotoxicity toward eukaryotic cells and possibly improved antimicrobial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic antimicrobial nanoparticles consisting of CSA-124 bound on a silver shell with a maghemite core were successfully synthesized and introduced as a novel multifunctional theranostic conjugate by Hayes et al [88,101]. Confocal imaging showed that the nanoparticles displayed higher selectivity for S. aureus than E. coli.…”
Section: Use Of Ceragenins In Imaging Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous published reports related to activity of CAPs at infection sites revealed synergism or additive interactions with other host-secreted antibacterial agents. 59,60 Recent studies confirm that ceragenins also exhibit a synergistic effect with other antibacterial agents such as cefepime and ciprofloxacine. 41,61 Ruden et al 23 revealed that silver nanoparticles act synergistically with polymyxin B.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, elevated eDNA and NET levels and their accumulation in biological fluids is a factor activating innate immune responses, which considerably affect the development of such diseases as asthma and chronic obstructive pulmonary disease [48], periodontitis [49], antineutrophil cytoplasmic antibody-associated vasculitis (AAV) [29], or cancerassociated thrombosis [50]. Quantitative analysis of the physical chemistry of polyelectrolytes has been useful for designing possible countermeasures to release endogenous antimicrobial peptides trapped in the polyelectrolyte bundles present in purulent fluids [5,45,[51][52][53][54][55][56]. Better penetration through this complex network might be achieved using a nanotechnology approach.…”
Section: Condensation Of Dna By Cationic Peptidesmentioning
confidence: 99%